Update on Canine and Feline Blood Donor Screening for Blood‐Borne Pathogens. (January 2016) - Wardrop, K.J.; Birkenheuer, A.; Blais, M.C.; Callan, M.B.; Kohn, B.; Lappin, M.R.; Sykes, J.
Abstract : An update on the 2005 American College of Veterinary Internal Medicine (ACVIM) Consensus Statement on blood donor infectious disease screening was presented at the 2015 ACVIM Forum in Indianapolis, Indiana, followed by panel and audience discussion. The updated consensus statement is presented below. The consensus statement aims to provide guidance on appropriate blood‐borne pathogen testing for canine and feline blood donors in North America.